Varicella‐zoster virus encephalomyelitis with a prominent demyelinating component. Issue 6 (26th June 2015) - Berth, Sarah; Carbunar, Olimpia; Yang, Ning Sarah; Fredericks, Brian; Lipton, Howard L.; Valyi‐Nagy, Tibor
Abstract : The histopathologic presentation of varicella‐zoster virus (VZV) infection of the central nervous system is varied and is not well understood. Here we report a case of VZV encephalomyelitis with prominent demyelinating pathology in a patient with a history of follicular lymphoma treated with allogeneic stem cell transplantation. The patient presented with waxing and waning bilateral limb weakness and mental status changes. MRI showed leptomeningeal, peripheral spinal cord and periventricular cerebral white matter lesions in the brain, and polymerase chain reaction on cerebrospinal fluid detected VZV DNA. The patient expired from developing atrial fibrillation that rapidly progressed to ventricular fibrillation 10 days after admission to our hospital. Autopsy revealed macrophage‐rich areas of demyelination in the spinal cord and cerebrum with relative preservation of axons associated with inclusion bodies and positive immunostaining for VZV. This case represents a rare example of VZV encephalomyelitis presenting with a predominantly demyelinating, "multiple sclerosis‐like" pathology. The clinical and histopathologic findings and relevant literature are presented and discussed.